Reliability of the high-speed camera-based system (HSC-Kinovea) for lower-limb explosive strength endurance assessment in athletes - Freitas-Junior, C. G.; Paes, P. P.; Fortes, L. S.; da Silva, A. J.; Costa, M. C.; Lima-Junior, D. A.; Santos, T. M. (Journal of Physical Education, 2020)
The present study verified the reliability of the high-speed camera-based system (HSC-Kinovea) in the lower-limb explosive strength endurance assessment in athletes. Eleven male volleyball players (21.8 ± 2.9 years; 186.3 ± 6.2 cm and 82.3 ± 11.0 kg) participated in the intermittent vertical jumping test in two days. The test was filmed and later analyzed using Kinovea 0.8.15 software to obtain the mean and peak power variables. Regarding reliability, the intra-class correlation coefficient, the typical error of measurements, and Bland-Altman plots were used. The method presented satisfactory values for inter and intra-class correlations (? 0.88). The typical values error of measurement presented in the inter-rater analysis was 0.95 W.kg-1 and 0.59 W.kg-1 for the peak and the mean power, respectively. In the intra-assessment analyses, the typical measurement error values were 7.02 W.kg-1 and 5.66 W.kg-1 (test-retest) and 1.59 W.kg-1 and 0.24 W.kg-1 (duplicates videos) for peak and average power, respectively. The HSC-Kinovea system is reliable for assessing the variables of the explosive strength endurance in athletes.